2019
DOI: 10.1002/jrs.5654
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative surface‐enhanced Raman spectroscopy enhancement in Au nanorod/SiO2 nanoparticle solutions

Abstract: Surface‐enhanced Raman spectroscopy (SERS) signals in liquid state are significantly enhanced by utilizing cooperative interaction between metal surface plasmon and dielectric resonance. Raman signals from the diluted solutions are very weak even if they are amplified by SERS using Au nanorods. When SiO2 nanoparticles are added together with Au nanorods, however, Raman intensity increased by three order comparing with that of system containing only Au nanorods. Finite‐difference time‐domain simulations show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…During the past decades, a plethora of studies have been conducted on SERS, , many of which are devoted to the increase of the SERS enhancement factor. The enhancement factors of as high as ∼10 6 have been realized in Au-NR-based SERS systems .…”
Section: Applicationsmentioning
confidence: 99%
“…During the past decades, a plethora of studies have been conducted on SERS, , many of which are devoted to the increase of the SERS enhancement factor. The enhancement factors of as high as ∼10 6 have been realized in Au-NR-based SERS systems .…”
Section: Applicationsmentioning
confidence: 99%
“…The maximum enhancement ratio of Raman intensity was up to 14.6 using 4.94-μm diameter PS microspheres (Yan et al, 2015). These results promote the research interest in coupling of DMs to metallic SERS substrates to further boost SERS sensitivity (Lu et al, 2009;Le Beulze et al, 2017;Nam et al, 2019;Hong et al, 2020). For example, Wang et al deposited a silver layer onto a DMs surface using electron beam evaporation.…”
Section: Introductionmentioning
confidence: 77%
“…However, suppressing short‐range, chemical enhancement effects in SERS proved challenging due to unavoidable charge‐transfer interactions between analyte and the SERS platforms. Nam et al [ 33 ] described cooperative SERS enhancement in Au nanorod/SiO 2 nanoparticle solutions. They found that when SiO 2 nanoparticles are added together with Au nanorods, Raman intensity increased by three orders compared with that of systems containing only Au nanorods.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%